Sovereignty and Survival: The Pakistani Context - Nasir, Mehak (Journal of Development and Social Sciences, 2025)
Employing a critical lens, the changing concept of sovereignty in geopolitics is analyzed and with special focus the obstacles experienced by Pakistan are compared to the global examples. Basically, the goal is to ascertain the manner in which sovereignty is asserted, kept or dilated in presence of foreign pressure, geopolitical tensions and inner instability. Sovereignty remains a defining factor in a state’s ability to exercise independent decision-making, yet it is often challenged by external interventions, economic dependencies, and internal governance failures. The paper creates an understanding of leadership strategies, policy options and resistance models of different countries towards reinforcing their sovereign power, through qualitative analysis. Methodologically, it employs political discourse analysis, analysis of recent diplomatic events and frameworks of state policy to describe patterns of sovereign assertion and erosion. The results show that powerful states commonly use ideological or military means to ensure or expand sovereignty, while smaller countries or those that are economically dependent, must struggle more to exercise this right. Strategic defiance is shown by countries like Iran and China in resisting outside interference. This provides context by placing these insights in relation to Pakistan’s unique geopolitical position, economic vulnerabilities and policy inconsistencies and identifies challenges and potential strategies to reinforce Pakistan’s sovereignty. The conclusion then states that for Pakistan to uphold its sovereign authority, it has to follow all of it; may it be a self-reliant economy, institutional reform and foreign policy continuity based on its own national interest. This research helps to discuss how important as part of sovereignty pointing the internal governance and external pressure in the formation of state legitimacy. It shows a nuanced understanding of sovereignty as being about more than territorial control and of resilient leadership, strategic autonomy and capable diplomacy. Proposed recommendations are not part of this research.